EFFICACY OF THIONONTRITE-S FOR PREVENTION OF METABOLIC LIVER DISEASE IN CATTLE - Ye. V. Tyapkina; M. P. Semenenko; Ye. V. Kuzminova; A. A. Abramov (Ветеринария сегодня)
The study data of the efficacy of thionontrite-S-complex preparation in the prevention of metabolic liver disease of cattle are presented. Administration of the preparation to 6–7-month-old cows in dry period for two weeks at a dose of 0.3 g/kg of body weight corrects biochemical homeostasis and prevents the development of pathogenetic shifts during metabolic liver disease. Disease symptoms faded on Day 12–14, preventive efficacy was 90%. In the control group 55% of cows demonstrated the disease symptoms. The use of thiononitrite-S promoted an increase in the protein-synthesizing function of the liver; in particular, an increase in the level of total protein was 8.8% against the baseline indicators in the experimental group. The increase in glucose level with respect to baseline indicators in the experimental group was 26.6%, in the control group this parameter decreased by 6.7%. The preparation restored functional and barrier properties of the liver, normalized the enzyme-forming function. At the end of the experiment the level of alanine aminotransferase in the first group was 1.8 times less than the control levels, the level of aspartate aminotransferase was 1.6 times lower than the negative control levels. The positive effect of thionontrite-S was also observed with regard to pigment metabolism; the concentration of total bilirubin in the experimental group was within physiological limits (4.28 ± 0.55 µM/l), whereas in the control group hyperbilirubinemia was 1.6 times higher than the upper limit of normal. Improvement of biochemical parameters in the experimental group correlated with a decrease in the level of medium-mass molecules and peroxidation products of unsaturated fatty acids. The decrease in the level of average weight molecules in experimental cows at a wavelength λ = 254 nm was 8.3% and at a wavelength λ = 280 nm – 10%. In the experimental group, the level of diene conjugates decreased by 14.3% with regard to baseline indicators, ketodienes – by 26.3%, malondialdehyde – by 8.9% and fluorescent Schiff bases – by 18.2%.